Porous Carbon Nitride Thin Strip: Precise Carbon Doping Regulating Delocalized π‐Electron Induces Elevated Photocatalytic Hydrogen Evolution. Issue 11 (18th February 2021) - Li, Qi; Zhang, Luoming; Liu, Jianan; Zhou, Jing; Jiao, Yanqing; Xiao, Xudong; Zhao, Chen; Zhou, Yang; Ye, Sheng; Jiang, Baojiang; Liu, Jian
Abstract: The photocatalytic efficiency of polymeric carbon nitride is hampered by high carrier recombination rate and low charge transfer. Herein, these issues are addressed by constructing 1D strip‐like carbon nitride with a large π‐electron conjugated system from carbon‐doping, realizing the synchronization control of its electronic structure and morphology. Nicotinic acid, a monomer with the carboxyl group and pyridine ring, and melamine are selected for assembling the strip‐like supramolecular via hydrogen bond under hydrothermal process. Both peripheral pyridine unit and hydrogen bond have significant effect on self‐assembly process of nicotinic acid and melamine along one dimension to form a strip‐like precursor. Subsequently, 1D thin porous strip‐like carbon nitride is obtained by calcination treatment of precursor. The as‐prepared 1D strip‐like carbon nitride with effective π delocalization from carbon‐doping and porous structure can accelerate charges and mass transfer and provide extra active sites. Both theoretical and experimental results demonstrate that carbon doping (pyridine heterocycle) narrows the bandgap via manipulating the band position and increases the π electron density. Thus, the 1D porous thin strip‐like carbon nitride realizes compelling hydrogen evolution rate (126.2 µmol h −1 ), far beyond (≈18 fold) the value of polymeric carbon nitride (PCN) (7.2 µmol h −1 ) under visible light irradiation. Abstract : 1D strip‐like carbon nitride (CN) with a large π‐electron conjugated system realizes the synchronization control of its electronic structure and morphology, which improves the separation efficiency of photogenerated charge carriers. Thus, such strip‐like carbon nitride exhibits a significant enhancement in photocatalytic activity with the hydrogen evolution rate of 126.2 µmol h −1, about 18 times higher than that of bulk CN.